Randomized clinical trial on the use of a colon-occlusion device to assist rectal washout - Cordewener, Carolin; Zürcher, Manuel; Müller, Philip C.; Müller, Beat P.; Zerz, Andreas; Linke, Georg R.; Steinemann, Daniel (Surgical endoscopy, 2021)
Transrectal Natural Orifice Transluminal Endoscopic Surgery is currently limited by the inherent risk of surgical site infection due to peritoneal contamination after rectotomy. Coloshield has been developed as a temporary colon occlusion device to facilitate rectal washout. However, effectiveness and safety has not been evaluated in humans.
Online publiziert: 23. September 2020
Gesehen am 05.09.2021